Analisis Wacana Kritis Iklan Sirup Marjan Tahun 2025 Episode 1 Kajian Metafora Multimodal - Febby Indriani; Malan Lubis; Syairal Fahmy Dalimunthe (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study uses Critical Discourse and Multimodal Metaphor analysis to examine how the meaning of advertisements is constructed through the interaction of various communication modes, namely visual, verbal, audio, and movement. The Marjan Syrup Episode 1 advertisement displays symbols that reinforce the image of Marjan as part of the community's fast-breaking ritual, using metaphors to emphasize the importance of consumption experiences, togetherness, and spiritual values. One of the main findings is the use of words and visuals that position the consumer as the "king" and Marjan as "wealth", which creates an emotional connection and promotes the experience as a satisfying one. The advertisement also depicts the challenges faced by society through visual and audio elements that create a dramatic atmosphere, reminding the audience about the dangers of dependence on technology.